THE DEVELOPMENT OF EU CYBERSECURITY POLICY: FROM A COORDINATING ACTOR TO A CYBER POWER? - Kadri Kaan Renda (Ankara Avrupa Çalışmaları Dergisi)
The aim of the article is to elaborate on the institutional and normative evolution of the European Union (EU) cybersecurity policy. The article primarily argues that the EU’s approach to cyberspace has recently focused on economic and security concerns. Secondly, the article contends that the actorness of the EU in the cyberspace has been evolved from a coordinating role to a more powerful one. The article is structured as follows: In the first part of the article, the literature on the EU’s actorness in cyberspace is reviewed. In the second part, the institutional and normative development of EU cybersecurity policy is evaluated. Three strategy papers published by the European Commission in 2013, 2017, and 2020 are elaborated, respectively.